(untitled) (Journal of Global Humanities and Social Sciences, 2023)
In modern society, rural areas still occupy a vast population and land resources, but have long been plagued by insufficient financial services, With the development of society, the demand for financial services from rural residents and enterprises has gradually increased, and this growth in demand has given rise to the application of financial technology in rural finance. Moreover, along with the rise of the global wave of digitalization, the popularization of smartphones, the expansion of Internet coverage, and the development of digital payment technology have created favorable conditions for the application of fintech in rural areas, and rural residents have more digital channels to access financial services. Based on this, the article conducts research on the mechanism of fintech-enabled rural finance, elaborates in detail on the cooperation between fintech and financial institutions and fintech innovation, and focuses on the path of fintech-enabled rural finance high-quality development, to provide some suggestions for your reference.